PENGARUH KEMAMPUAN LITERASI TERHADAP PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI SEBAGAI SUMBER BELAJAR DI SMA KABUPATEN PASANGKAYU - Nasria; Sapto Haryoko; Mustari Lamada; Hasanah Nur (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2024)
This research aims to provide an overview of Information and Communication Technology (ICT) Literacy and the utilization of ICT as a learning resource in high schools in Pasangkayu Regency.where in Pasangkayu district there is are 12 high school and Additionally, it seeks to examine the influence of ICT literacy on the utilization of ICT as a learning resource. The research employs an ex-post facto research method. The total population is 4027 individuals, and a sample of 220 participants is drawn through Probability Sampling. The instruments used include tests and questionnaires. Prerequisite tests involve assessing normality and linearity. Hypothesis testing employs a simple linear regression test. The research findings indicate that: (1) ICT Literacy is categorized as